44th AIAA/ASME/SAE/ASEE Joint Propulsion Conference &Amp;amp; Exhibit 2008
DOI: 10.2514/6.2008-5287
|View full text |Cite
|
Sign up to set email alerts
|

Angularly-Resolved ExB Probe Spectra in the Plume of a 6-kW Hall Thruster

Abstract: An E×B probe was used to characterize the angular distribution of multiply-charged ions in the plume of a 6-kW Hall thruster operating at discharge voltages of 150-600 V, and anode mass flow rates of 10-30 mg/s. The local ion current fractions were measured in conjunction with ion current density at several locations from 0-30º from thruster centerline, and axial locations of 8, 10, and 12 thruster diameters. Typically the fraction of Xe 2+ increased by the drop in Xe 1+ , while Xe 3+ remained approximately co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 16 publications
2
30
1
Order By: Relevance
“…Species current fractions were corrected for the attenuation of beam ions due to CEX collisions using the procedure outlined by Shastry et al [63]. Conclusions from a recent study of angularly resolved ExB probe spectra using this thruster model asserted that a measurement on channel centerline was representative of the species fractions throughout the plume and deviated from plume averaged results by less than 1.5% over a wide range of thruster operating conditions [64]. In this case study, ExB and RPA results are from channel centerline measurements, and variations in the plume are accounted for in the specified uncertainty.…”
Section: A Experimental Apparatusmentioning
confidence: 99%
See 1 more Smart Citation
“…Species current fractions were corrected for the attenuation of beam ions due to CEX collisions using the procedure outlined by Shastry et al [63]. Conclusions from a recent study of angularly resolved ExB probe spectra using this thruster model asserted that a measurement on channel centerline was representative of the species fractions throughout the plume and deviated from plume averaged results by less than 1.5% over a wide range of thruster operating conditions [64]. In this case study, ExB and RPA results are from channel centerline measurements, and variations in the plume are accounted for in the specified uncertainty.…”
Section: A Experimental Apparatusmentioning
confidence: 99%
“…C2, this range is approximately 3 to 21 deg. Near-and far-field plume measurements of the 6 kW Hall thruster [64], the SPT-100 [45,66], and the BHT-200 [73] Hall thruster found that the ion species populations did not significantly change within 15 deg from thruster centerline, and the fraction of Xe 2 increased sharply by approximately 5% at 20 deg. These changes in ion species composition have a negligible effect on the value of hcosi mv , thus enabling the approximation of equivalence between momentumweighted divergence and charge-weighted plume divergence as measured with a Faraday probe.…”
Section: Appendix C: Comparison Of Momentum-weighted and Charge-weighmentioning
confidence: 99%
“…This was a surprising result (though one that has also been reported by Reid et al 13 ) since in that orientation the probe has a direct line-of-sight only to the ceramic cover on the inner magnetic pole. It is therefore not obvious from which source volume the ions collected by the ExB probe originated.…”
Section: Exb Probementioning
confidence: 57%
“…It is therefore not obvious from which source volume the ions collected by the ExB probe originated. Reid et al 13 recommended weighting current fractions measured with the ExB probe with current density measurements when integrating over angles to determine plume-averaged current fractions. Adoption of this procedure implies that the fraction of ions detectable by the highly collimating ExB probe at a given angle varies with angle, thereby requiring a second probe with wider angular acceptance to produce the weighting factors.…”
Section: Exb Probementioning
confidence: 99%
“…Thus, not correcting measurements with κ SEE may lead to overprediction of local ion current density by 5 to 10%, and it should be accounted for in the data analysis and/or error assessment. However, the spatial variation of ion species composition in the central plume is not expected to have a significant effect on the value of κ SEE ; therefore, a single measurement of ion species current fraction in the central core is sufficient to calculate κ SEE [82] for evaluation of ion beam current and divergence. The population of multiply charged ions may increase beyond the central core; thus, it is advised to incorporate local values of ion species current composition in evaluations of local spacecraft plume interactions on the plume periphery.…”
Section: A Ion Current Densitymentioning
confidence: 99%